BIMBINGAN TEKNIS PENANAMAN HIJAUAN PAKAN TERNAK (HPT) DI DESA WONUA MORINI KECAMATAN PALANGGA KABUPATEN KONAWE SELATAN - Abadi, Musram; Arsad Sani, La Ode; Syamsuddin, Syamsuddin; Rusdin, Muh.; Pagala, Amrullah; Nafiu, La Ode; Selamet Aku, Achmad; Astuty Auza, Fuji; Fitrianingsih, Fitrianingsih; Sahaba, La; Surahmanto, Surahmanto; Yaddi, Yamin; Indi, Amiluddin (Universitas Halu Oleo, 2023)
The Ministry of Agriculture designated South Konawe Regency as a source area for Balinese cattle through Minister of Agriculture Decree (Kepmentan) No. 803/Kpts/PK.030/12/2016 where one of the buffer areas is Palangga District. The main problem for breeders in Palangga District is the limited forage during the dry season. In the dry season, breeders only provide minimal feed without paying attention to the quality, quantity, and efficiency of the provision. The lack of awareness among breeders regarding the provision and utilization of quality HPT in sufficient quantities has caused the majority of breeders to provide forage of low quality to the livestock they keep. The aim of this activity is to help farmers produce optimal production by handling animal feed problems. The results that have been achieved in this Thematic KKN are increasing the knowledge and understanding of farmers raising livestock farmers' awareness of providing and utilizing quality HPT in sufficient quantities and ensuring its continuity throughout the year so that livestock productivity can be maintained and increased.